LEARNING ARABIC VOCABULARY FROM THE QURAN TO FACILITATE EARLY ARABIC SPEAKING SKILLS AND MEMORIZING QURAN AT BAITURRAHMAN KINDERGARTEN IN MALANG CITY - Mufidah, Zuhrotul (Sekolah tinggi ilmu ekonomi pemuda, 2024)
Learning Arabic can indeed be easily initiated from an early age by acquiring Arabic vocabulary from the commonly heard Quran. It has been proven that learning Arabic vocabulary from the Quran facilitates children in memorizing the Quran, as they memorize by envisioning the meanings of the Quranic vocabulary they are reciting. This serves as the rationale for researchers to investigate how Arabic language learning can be conducted by utilizing vocabulary from the Quran, aiming to ease students in both speaking Arabic and memorizing the Quran. Consequently, students become accustomed to listening to Arabic vocabulary and understanding its meanings through presented images without initially mentioning their meanings. With this direct method, students find it easier to recall the vocabulary provided. This research adopts a qualitative descriptive method and yields insightful findings that are highly beneficial to Quranic institutions as considerations for incorporating Arabic language learning before Quran memorization